2006
DOI: 10.1007/s11103-005-5022-9
|View full text |Cite
|
Sign up to set email alerts
|

Wood Formation from the Base to the Crown in Pinus Radiata: Gradients of Tracheid Wall Thickness, Wood Density, Radial Growth Rate and Gene Expression

Abstract: Wood formation was investigated at five heights along the bole for two unrelated trees of Pinus radiata. Both trees showed clear gradients in wood properties from the base to the crown. Cambial cells at the base of the tree were dividing 3.3-fold slower than those at the crown, while the average thickness of cell walls in wood was highest at the base. Cell wall thickness showed an overall correlation coefficient of >0.7 with wood density in both genotypes. Microscopic examination of developing tracheids showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 32 publications
5
44
0
2
Order By: Relevance
“…The P. glauca a-tubulin gene (TUA2) is highly similar to sequences that have been linked to the formation of cortical microtubules in P. taeda (González-Martínez et al 2007), developing xylem-preferential transcript accumulation in P. radiata (Cato et al 2006), ESTs that are unique to xylem librairies in Populus (Pilate et al 2004), and transcripts levels that correlated with auxin concentration in developing secondary xylem in P. tremula x tremuloides (Nilsson et al 2008). A b-tubulin gene was shown to be preferentially expressed in xylem in Eucalyptus (Paux et al 2004).…”
Section: Resultsmentioning
confidence: 97%
“…The P. glauca a-tubulin gene (TUA2) is highly similar to sequences that have been linked to the formation of cortical microtubules in P. taeda (González-Martínez et al 2007), developing xylem-preferential transcript accumulation in P. radiata (Cato et al 2006), ESTs that are unique to xylem librairies in Populus (Pilate et al 2004), and transcripts levels that correlated with auxin concentration in developing secondary xylem in P. tremula x tremuloides (Nilsson et al 2008). A b-tubulin gene was shown to be preferentially expressed in xylem in Eucalyptus (Paux et al 2004).…”
Section: Resultsmentioning
confidence: 97%
“…Previous research has suggested that the gradients of wood properties found in radiata pine are underpinned by differences in the rate of cambial cell division, differences in the rate and duration of tracheid wall thickening, and differences in gene expression (Cato et al 2006). In the radial direction, wood density increased rapidly with increasing ring number from the pith before reaching a quasiasymptotic value such that little change in density occurred after approximately ring 20.…”
Section: Discussionmentioning
confidence: 99%
“…Especially, using cryosectioning and RNA-Seq methods, Xu et al (2016) compared the transcriptome of vascular cambium tissue in Cunninghamia lanceolata at juvenile, transitional, and mature stages to study the effects of age on cambium activity. Within-tree transcriptome and proteome profiling in wood-forming tissues based on changes of cell size and other wood properties have also been studied (Cato et al 2006;Garces et al 2014;Kumar et al 2009;Lorenz and Dean 2002;Paiva et al 2008;Ranik et al 2006). However, the regulatory network of age effects on the processes of wood formation remains poorly understood, and systematic investigation at the genome level is still needed.…”
Section: Communicated By F Gugerlimentioning
confidence: 99%